Importance of illustrating art objects (drawing, painting or sculpture) on the front cover - Valença, Marcelo Moraes; Andrade, Juliana Ramos; Peres, Mario Fernando Prieto (Headache Medicine, 2021)
Years ago, we created a section in Headache Medicine entitled NeuroArt1-3 to value artistic expression that represented the specialty of the study of diverse headache subtypes. As the current trend is to put on the front cover a figure representing the specialty or a theme covered in the issue, we have also used images related to Headache Medicine to illustrate our front covers.